Mierniki finansowe stosowane do pomiaru działalności ośrodków odpowiedzialności w wielonarodowych przedsiębiorstwach zdecentralizowanych (w świetle badań ankietowych) - Makowska, Ewa (Financial Measures Used by Multinational Enterprises to Evaluate the Performance of the Responsibility Centres (Based On Survey Research), 2005)
The main objective of this paper is the presentation of financial measures that are used to determine the performance of responsibility centres in the surveyed multinational enterprises. Various types of responsibility centres have different level of freedom in choosing the methods and means leading to the completion of assigned objectives. Selected results of the carried out survey research are presented in this paper.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 286-294